Treatment compliance among lung cancer patient in Malaysia - Ng, Teck Han; How, Soon Hin; Kuan, Yeh Chunn; Abdul Rani, Mohammed Fauzi (2008)
INTRODUCTION Lung cancer remains one of the most common causes of cancer death. In our experience, a high proportion of patients did not turn up for their follow up. OBJECTIVE To determine the prevalence, risk factors, reasons for defaulting follow up and treatment among patients with lung cancer.